"A Swedish Voltaire" The Life and Afterlife of Ingemar Hedenius, 20th-Century Atheist. (23rd April 2018) - Jansson, Anton
Ingemar Hedenius (1908–1982) was a professor of philosophy, and one of Sweden's most famous public intellectuals in the decades following the Second World War. This was primarily due to his 1949 work Tro och vetande (English: Belief and Knowledge ) in which he criticized religion, and his subsequent activity in the promotion of atheism and criticism of the relationship between church and state. This article engages with Hedenius's life and works, but has a particular focus on his "afterlife". The article utilizes theories of cultural memory to examine how Hedenius has been remembered since his death. I argue that Hedenius and his Tro och vetande in Sweden have taken the role of a node, or inescapable orientation point, of discussions of atheism, belief and knowledge, and the validity of Christian truths. Hedenius's memory continues to loom large over religion and nonreligion in Sweden to this day. The material used as primary sources in this article include scholarly works of philosophy, theology and history, by renowned Swedish academics, but it also contains interpretations of Hedenius in the wider public debate, not least as expressed by the Swedish Humanist Association, who regard him as a main inspiration for their activities.